Using Antconc Software As English Learning Media: The Students’ Perception - Eri Ester Khairas (Epigram, 2019)
The use of techonology for a method in learning is rapidly developed and effect the students’ learning process. This research is aimed to find out about the perception of college students about a learning method of English by using a software named AntConc. The data were collected through questionnaires divided into pre-questionnaire and post-questionnaire. Pre questionnaire was about students’ perception towards AntConc software itself and the post questionnaire was about students’ perception using the software. The respondents were 51 students of Engineering Department, Politeknik Negeri Jakarta.. This research shows that Antconc software can be an alternative method to enhance students learning of English by using some tools on its software.